(1/7)2 = 2/7
(1/4)2 = 2/4 = 1/2
(3/5)2 = 6/5= 1 1/5
(1 1/3)2 = 8/3 = 2 2/3
а) -6(х+2)=4х-17
-6х-12=4х-17
-6х-4х=-17+12
-10х=-5
10х=5
х=0,5
б)(18-19)-(4-7х)=-73
-1-4+7х=-73
-5+7х=-73
7х=-73+5
7х=-68
х=-9,7142
в)10х+3(7-2х)=13+2х
10х+21-6х=13+2х
4х+21=13+2х
4х-2х=13-21
2х=-8
х=-4
г)-3(4-5х)+2(3-6х)=-3,9
-12+15х+6-12х=-3,9
3х-6=-3,9
3х=-3,9+6
3х=2,1
д)9(х-1)=х+15
9х-9=х+15
9х-х=15+9
8х=24
х=3
е)(11х+14)-(5х-8)=25
11х+14-5х+8
6х+22=25
6х=25-22
6х=3
х=0,5
ё)12-4(х-3)=39-9х
12-4х+12=39-9х
24-4х=39-9х
-4х+9х=39+24
5х=63
х=12,6
ж)2(3х+5)-3(4х-1)=11,8
6х+10-12х+3=11,8
-6х+13=11,8
-6х=11,8-13
-6х=-1,2
6х=1,2
х=0,2
Пошаговое объяснение:Если я всё правильно сделал в номере Ж то тогда у тебя ошибка в задании
(1/7)*2=2/7
(1/4)*2=2/4=1/2
(3/5)*2=6/5=1 1/5
(1 1/3)*2=8/3=2 2/3
Пошаговое объяснение: